Whole-genome sequencing disproves two suspected transmission events of blaNDM between Pseudomonas aeruginosa and Enterobacterales in hospitalized patients - Kocer, Kaan; Boutin, Sébastien; Probst, Katja; Heeg, Klaus; Nurjadi, Dennis (The journal of hospital infection, 2020)
New Delhi metallo-β-lactamase (blaNDM) acquisition by Gram-negative bacteria is a primary concern due to its broad-host-range distribution. This study investigated two potential in-vivo horizontal gene transfers (HGTs) of blaNDM between Enterobacterales and Pseudomonas aeruginosa, initially indicated by polymerase chain reaction. Whole-genome sequencing showed independent parallel acquisition of two different blaNDM variants (NDM-1 and NDM-5) in P. aeruginosa and Enterobacterales, respectively. The data show that short-read sequencing provides the necessary resolution to confirm or dispute HGT by the comparison of genetic elements surrounding the gene of interest, and thus provide a timely response to potential outbreaks.
Im Titel ist "NDM" tiefgestellt
Gesehen am 12.11.2020